Libertà di religione e sicurezza. Il test del terrorismo (Stato, Chiese e pluralismo confessionale, 2023)
Freedom of Religion and Security. The Test of TerrorismABSTRACT: The relationship between the rights of freedom, including that of religion, and security has always been controversial and currently even more because of the fear, perceived even when not real as in Italy, of the jihadist terrorism, to which there is a risk of sacrificing the freedom to profess and propagate the Islamic religion. This essay tests the Italian jurisprudence in this regard and argues the need for balancing so that the security requirements are guaranteed by the counter-limit of the supreme principles of the Constitution and in particular by the human dignity.SOMMARIO: 1. Paura - 2. Sicurezza - 3. Libertà - 4. Terrorismo - 5. Bilanciamento.